Suriname-Guyana maritime and territorial disputes : a legal and historical analysis - Donovan, Thomas W. (2003)
Suggests what an international tribunal would decide if it was appointed to settle the dispute. Looks at what legal and historical precedents the tribunal should consider in arriving at its decision.